Green extraction cascade of UV-absorbing compounds, alginate, and fucoidan from Sargassum using ethanol and natural deep eutectic solvents - Santiago Guerrero-Higareda; Danay Carrillo-Nieves (Heliyon)
The objective of this study was to evaluate Caribbean Mexican seaweed as a raw material for the production of fucoidans, alginates, and bioactive extracts with antioxidant activity, total flavonoid content, total phenolic content, and UV absorbance. Extractions were first performed using varying ethanol concentrations and maceration times, with the optimal treatment selected based on its superior antioxidant activity, flavonoid and phenolic contents, and UV absorbance. The solid fraction from this treatment was then subjected to extraction using green solvents, specifically natural deep eutectic solvents (NADESs) and ultrasound-assisted extraction (UAE), to isolate alginate and fucoidan. The green extraction cascade enables the recovery of multiple value-added products from each fraction, showcasing both versatility and sustainability. The new DES combination yielded a high amount of crude fucoidan (0.4103 ± 0.0042 g g⁻1 dry algae), exceeding the yields reported in previous studies. FTIR-ATR analysis confirmed that the extracted fucoidan structure was consistent with that of Sargassum spp., although further purification and characterization are needed to determine whether its known bioactive properties are preserved. All treatments exhibited strong UV-B absorbance, highlighting the potential of Sargassum extracts as sunscreen filters, with polyphenolic compounds being the primary contributor to UV absorption. Additionally, UV-A absorbance was correlated with flavonoid and carotenoid content, particularly in 50 % ethanol extracts. Future research should explore the potential of Sargassum for sunscreen applications and polysaccharide extraction, offering a sustainable solution to the environmental and economic challenges posed by annual Sargassum blooms in Mexico.